Medicines Procurement Practices in Public Sector - GP, Mohanta; R, Veena (Indian Journal of Pharmacy Practice)
Medicines are perhaps the most important medical intervention in health care delivery systems. Thus the availability and easy accessibility to quality medicines by the public is an important component in health care services. The non-availability of medicines demoralise the health work force and the health system looses credibility. The people will not use the system and the system may fail. Health system can not succeed unless the continuing availability of quality medicines is ensured. The component of the medicines in the overall health budget of the central and state governments is just around 12% and 10% respectively. Often the drug expenditure as percentage of health expenditure is as low as less than 2% in some states. Such small percentage of money allotment or spent on medicines requires careful planning on drug supply management in order to optimise the utilization of resources for ensuring availability of quality medicines in public health system.